A Descriptive Analysis of Psychosocial Factors Associated With Non- fatal Adolescent Suicide Attempts - Kiran Kumar K.; Fiaz Ahmed Sattar; Pradeep Veluswamy; Swapna Bondade (International Journal of Medical Research and Review, 2016)
Introduction: Adolescence is the tender, vulnerable transition period with umpteen challenges and individual vulnerability. Various Psychosocial factors play a determinantal role in the genesis of adolescent suicide attempts and the present descriptive study tries to analyze some common psychosocial factors in cases of non-fatal adolescent suicide attempters.Method: Fifty subjects were recruited in the study. Detailed assessment of psychiatric morbidity and attempted suicide was done by clinical interview and validated by M.I.N.I.- KID, Beck Suicide Intent Scale and Adolescent Suicide Assessment Protocol-20. Psychosocial factors associated with the attempt were documented with the semi-structured proforma and descriptive statistical analysis was done with the help of SPSS version 15.Results: Majority of the suicide attempters were in the age group of 18-19 years and females (54%) outnumbered males (46%). Most of the subjects were single (88%), Hindu (86%) by religion, belonged to middle socioeconomic class (82%) and were from the urban background (80%). Two third of them belonged to nuclear family and half of them were students. In our evaluation of various psychosocial factors, 76% of subjects were found to have psychosocial stressor, in that 10% had two or more stressors. Family related factors were the most common (60%) followed by college related factors (26%) in which most common was love failure (12%).Conclusion: A sizeable proportion of subjects had various psychosocial factors associated with non-fatal adolescent suicide attempts and emphasis on these factors can help in prevention and hence monitoring of at-risk adolescents.